EFFECTS OF THE INDIGENOUS COMMUNICATIVE FRENCH TEACHING MODEL ON STUDENTS’ AFFECTIVE RESPONSE TO FRENCH - N., Kanno T.; Nkechi, Ezenwa Prisca Colette (Sokoto Educational Review, 2020)
This quasi-experimental study set out to explore the effects of the Indigenous Communicative French Teaching Model (INCOFT Model) on students’ interest in and attitude to French. Guided by one null hypothesis, the study had as its population two hundred and fifty-one thousand, eight hundred and seventy-three year two students in public junior secondary schools in Imo State. Sixty students of Urban Junior Secondary School Umuna, Orlu constituted the sample for the study. These were taught for six weeks in two intact classes constituting the experimental and control groups of thirty students each. An Affective Response to French Scale (AREFS) was the instrument for the study. It was validated using Cronbach Alpha Correlation Coefficient and a reliability index of 0.77 was realized. This test was administered to the subjects before and after the treatment. The data collected were analyzed using mean ratings and the t-test was used to test the hypothesis at 0.05 level of significance. The INCOFT Model was found to be effective in enhancing the students’ interest in and attitude to French. The researchers recommend, among other things, that teachers using the INCOFT model need to identify and use the techniques that most interest their students and motivate them to learn French.